2014
DOI: 10.1155/2014/959830
|View full text |Cite
|
Sign up to set email alerts
|

Trapa bispinosaRoxb.: A Review on Nutritional and Pharmacological Aspects

Abstract: Trapa bispinosa Roxb. which belongs to the family Trapaceae is a small herb well known for its medicinal properties and is widely used worldwide. Trapa bispinosa or Trapa natans is an important plant of Indian Ayurvedic system of medicine which is used in the problems of stomach, genitourinary system, liver, kidney, and spleen. It is bitter, astringent, stomachic, diuretic, febrifuge, and antiseptic. The whole plant is used in gonorrhea, menorrhagia, and other genital affections. It is useful in diarrhea, dyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 14 publications
1
36
0
Order By: Relevance
“…Preliminary qualitative chemical studies indicated the presence of lignan, isoflavones, phenolic contents, steroids, saponin, terpenoids, glycosides, tannins, flavonoids, and phenolic in the extract. And isoflavones, polyphenol, namely, lignan, are responsible for regulating the rat fertility [ 17 ]; maybe it is helpful for the regulating and enhancing the human fertility [ 17 , 19 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary qualitative chemical studies indicated the presence of lignan, isoflavones, phenolic contents, steroids, saponin, terpenoids, glycosides, tannins, flavonoids, and phenolic in the extract. And isoflavones, polyphenol, namely, lignan, are responsible for regulating the rat fertility [ 17 ]; maybe it is helpful for the regulating and enhancing the human fertility [ 17 , 19 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be achieved by molecular modeling studies involving interaction of bioactive phytochemicals from P. odoratissimus with their respective molecular and therapeutic targets. The extract of P. odoratissimus could be further explored in the future as a source of useful phytochemicals for the pharmaceutical industry [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aza-alkaloids display important biological and pharmacological properties including antimicrobial, anticancer, antiviral activities, and others. [5,17,[46][47][48][49][50] Steroidal alkaloids were first isolated from the skin glands of Salamandra in the mid-30s of the 20th century, [51] although they have been known since 1866. [52] Samanine (38) and samandarin (39) were isolated from the skin glands of Salamandra.…”
Section: Introductionmentioning
confidence: 99%
“…Floating leaves have rosette form, and leaflet is solid and triangular (5.2x6.4 cm) (Nedhuka & Kardyum, 2016). The leaves are dark green, and their bottom surface is reddish purple (Adkar et al, 2014;Zhu, 2016). The submerged stems cling to the soil by extending to 1-5 m along the roots (Adkar et al, 2014;Hummel & Kivrat, 2004).…”
Section: Introductionmentioning
confidence: 99%